Management of Personnel Administration through the Employee History Application System (SARIP) at the Tomohon Regional Personnel and Human Resources Development Agency - S. Deli Amelia Para; Abdul Rahman Dilapanga; Fitri Herawati Mamonto (Syntax Corporation Indonesia, 2022)
This study aims to describe the administration of personnel administration through the Employee History Application System (SARIP) at the Regional Personnel and Human Resources Development Agency of Tomohon City. This study uses qualitative research methods and uses data collection techniques: Observation, Interview, and Documentation. The primary data source for this research is the Tomohon City Government, in this case, the Civil Servant at the Tomohon City Regional Personnel and Human Resources Development Agency, and the secondary data sources are supporting documents, archives, and literature. The results of the study show that: Management of Personnel Administration through SARIP has not been carried out optimally, although the SARIP component is adequate, SARIP managers or users have not maximized their role through inputting data and personnel documents so that the number of employees whose data is inputted in SARIP has only reached approximately 38% of the total number of all Civil Servants in the Tomohon City Government. The results of the study concluded: (1) SARIP as a digital archiving forum is sufficient in terms of software components, hardware, and also networks but still needs to be improved on Human Resources as users. All components must work together so that Document Archiving through SARIP can be carried out; (2) The management of the promotion administration is quite helped by the existence of SARIP, but there are still frequent technical errors in data input and document uploads which become obstacles in the promotion process.